Проблеми впровадження «бережливого виробництва» на сучасних українських підприємствах - Харченко, І. В.; Kharchenko, I. (КНТУ, 2014)
Проаналізовано проблеми, з якими стикаються українські та закордонні промислові підприємства при впровадженні системи «бережливого виробництва». Запропоновано систему організаційно-планових нормативів, які допоможуть зменшувати витрати промислового підприємства при виготовленні продукції. The aim of this article is to describe the main prblems which Ukrainian enterprises face while introducing lean production on Ukrainian enterprises The article defines technical and organization problem, which must be solved in order introduce lean production. The author proposes the method and totality organization norms, which could minimize production costs. The method may be used in certain production conditions.
Problems in order introduce lean production on Ukrainian enterprises
Keywords: собівартості продукції; висока якість; організаційно-планові нормативи; система КПН; моделюючі алгоритми; organization production systems; just in time; introducing lean production; minimizing production costs; high quality; method and totality organization norms; simulation algorithms.